2020
DOI: 10.1177/2045125320950567
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic potential of microdosing psychedelics in depression

Abstract: Microdosing psychedelics is the repeated use of small doses of, for example, lysergic acid diethylamide (LSD) and psilocybin, typically for a few weeks. Despite the popular and scientific attention in recent years, and claims by users that it has therapeutic value in affective disorders like depression, little scientific knowledge is available to back this. The purpose of this review was to investigate whether there are scientific grounds to state that this practice could be helpful in the treatment of affecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 56 publications
(165 reference statements)
0
35
0
Order By: Relevance
“…In addition to usage at psychotomimetic doses, both ketamine and psilocybin have a long history of being self-adminstered at lower doses (colloquially referred to as "microdoses"), (Johnstad, 2018;Kuypers et al, 2019;Hutten et al, 2019;Polito and Stevenson, 2019;Rosenbaum et al, 2020). However, while there are a number of anecdotal reports describing beneficial effects of "micro" dose ketamine and psilocybin on mood and cognition, there are very few placebo controlled, scientific studies explicitly designed to investigate low doses of ketamine, and none explicitly using psilocybin (Kuypers et al, 2019;Kuypers, 2020). In the case of psilocybin, the actual doses are unknown since natural mushroom containing the agent are ingested.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to usage at psychotomimetic doses, both ketamine and psilocybin have a long history of being self-adminstered at lower doses (colloquially referred to as "microdoses"), (Johnstad, 2018;Kuypers et al, 2019;Hutten et al, 2019;Polito and Stevenson, 2019;Rosenbaum et al, 2020). However, while there are a number of anecdotal reports describing beneficial effects of "micro" dose ketamine and psilocybin on mood and cognition, there are very few placebo controlled, scientific studies explicitly designed to investigate low doses of ketamine, and none explicitly using psilocybin (Kuypers et al, 2019;Kuypers, 2020). In the case of psilocybin, the actual doses are unknown since natural mushroom containing the agent are ingested.…”
Section: Introductionmentioning
confidence: 99%
“…However, Bright et al (2021) found that microdosers had higher levels of depression and anxiety compared to a yoga control group. In a recent review of 14 microdosing studies, Kuypers (2020) observed that "while low LSD doses were experienced as pleasant, it was also shown that drug disliking and anxiety increased, and that a cycling pattern of depressive and euphoric mood changes can occur" (Kuypers, 2020, pp. 9-10).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, data and anecdotal reports concerning the physiological effects of administration of psychedelics in very low doses, or micro-dosing, have gained significant public attention. Micro-dosing of psychedelics refers to the ingestion of low to very low doses (5 and 10% of a standard hallucinogenic dose) on an established schedule (every other day) with the intention of avoiding hallucinogenic or short-term debilitating effects (Fadiman and Korb, 2019 ; Kuypers et al 2019 ; Kuypers, 2020 ; Liechti 2019 , Bershad et al 2019 Cameron et al 2020 ). However, regardless of the identity of the psychedelic, there are no scientifically established dose ranges that have been accepted for micro-doses of these substances (Kuypers et al 2019 ; Passie 2019 ; Lea et al 2020 ).…”
Section: Administration Of Dmtmentioning
confidence: 99%